2004
DOI: 10.1023/b:mcbi.0000041865.63445.40
|View full text |Cite
|
Sign up to set email alerts
|

Role of proteases in the pathophysiology of cardiac disease

Abstract: Cardiovascular disease is a major cause of death and thus a great deal of effort has been made in salvaging the diseased myocardium. Although various factors have been identified as possible causes of different cardiac diseases such as heart failure and ischemic heart disease, there is a real need to elucidate their role for the better understanding of the cardiac disease pathology and formulation of strategies for developing newer therapeutic interventions. In view of the intimate involvement of different typ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
37
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(38 citation statements)
references
References 162 publications
1
37
0
Order By: Relevance
“…The cleavage of intracellular target proteins by calpain may contribute to both programmed cell death and contractile dysfunction as part of pathological remodeling. In the heart, numerous studies have indicated that increased calpain activity might be a contributing factor to various pathological states, including MI, hypertensive cardiomyopathy, and ischemia-reperfusion injury (1,23,24,37,39,44,47). In the case of MI, the levels of both -and m-calpain isoforms were shown to increase in rats following left ventricular coronary artery ligation for 2 wk, and cardiac failure then developed by 8 wk (47) with profound cardiac remodeling and concomitant calpain activity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The cleavage of intracellular target proteins by calpain may contribute to both programmed cell death and contractile dysfunction as part of pathological remodeling. In the heart, numerous studies have indicated that increased calpain activity might be a contributing factor to various pathological states, including MI, hypertensive cardiomyopathy, and ischemia-reperfusion injury (1,23,24,37,39,44,47). In the case of MI, the levels of both -and m-calpain isoforms were shown to increase in rats following left ventricular coronary artery ligation for 2 wk, and cardiac failure then developed by 8 wk (47) with profound cardiac remodeling and concomitant calpain activity.…”
Section: Discussionmentioning
confidence: 99%
“…Calpain activation results in the cleavage of a number of specific cardiomyocyte proteins that might lead to subcellular remodeling and contractile dysfunction (44). Calpain-mediated proteolysis of contractile proteins, such as troponins, has been demonstrated in stunned myocardium (17).…”
Section: Discussionmentioning
confidence: 99%
“…This study will focus on one potential pathophysiologic mechanism of LV remodeling, changes in extracellular matrix (ECM) regulatory proteases. The matrix metalloproteinases (MMPs), and their tissue inhibitors, the TIMPs, constitute one important proteolytic pathway which can affect remodeling of the left ventricle by altering cardiomyocyte and/or ECM structure and composition (9)(10)(11)(12)(13). MMPs degrade fibrillar proteins, activate biologically important molecules, and modulate ECM remodeling (9,10,(12)(13)(14)(15)(16)(17)(18)(19).…”
Section: Introductionmentioning
confidence: 99%
“…In vivo, calpains are believed to function in myoblast fusion (12), long term potentiation (13), and cellular mobility (14). Unregulated calpain activity, secondary to intracellular calcium overload, is associated with several pathological conditions, including Alzheimer disease (15), animal models of cataract (16), myocardial (17), and cerebral ischemia (18).…”
mentioning
confidence: 99%